The Akebia Genus as a Novel Forest Crop: A Review of Its Genetic Resources, Nutritional Components, Biosynthesis, and Biological Studies - Huang, Ping; Zang, Fengqi; Li, Changhong; Lin, Furong; Zang, Dekui; Li, Bin; Zheng, Yongqi (Frontiers in Plant Science, 2022)
The genus Akebia belongs to the Lardizabalaceae family and comprises four species that are primarily distributed in East Asia. Plants of the Akebia genus comprise deciduous and semi-evergreen perennial twining vines that have been used in Chinese herbal medicine for at least 2,000 years. The plants of this genus have the potential to form a novel forest crop with high nutritional and economic value because their fruit has a delicious, sweet taste and rich nutrient components. In this study, we organized, analyzed, and evaluated the available published scientific literature on the botanical, ecological, and phytochemical characteristics of Akebia plants. Based on these studies, we briefly introduced botanical and ecological characteristics and focused on reviewing the development and utilization of wild genetic resources in the genus Akebia. We further explored the genus’ rich nutritional components, such as triterpenes, flavonoids, polyphenols, polysaccharides, and fatty acids, and their potential use in food and health improvement applications. In addition, several papers describing advances in biotechnological research focusing on micropropagation, nutrient biosynthesis, and fruit ripeness were also included. This review provides comprehensive knowledge of the Akebia genus as a new forest crop for food and fruit utilization, and we also discuss future breeding and research prospects.